2011
DOI: 10.1002/pssb.201100515
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphile replacement on carbon nanotube surfaces: Effect of aromatic groups on the interaction strength

Abstract: Carbon nanotubes (CNTs) were solubilized using akyl/polyglycerol amphiphiles. Similar cosurfactants, bearing different aromatic moieties between head and tail, were added to these samples. The interaction strength between these amphiphiles and CNTs changes depending on the inserted aromatic moieties. The insertion of a phenyl ring allows the amphiphile to replace the starting one indicating a higher interaction strength, while the insertion of a triazol pentagon does not, suggesting that the interaction streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Small aromatic moieties, for example, pyrene, perylene, porphirine, can replace alkyl chain to bring tubes in solution but the higher adsorption energy makes the surfactant efficiently stick on the nanotubes and more difficult to be desorbed and removed. The choice of the aromatic core impacts the nanotube‐surfactant interaction strength and how efficiently they can be replaced with other surfactants . By incorporating an azobenzene‐derivative between head and tail, we have even been able to trigger the micelle disruption and nanotube re‐aggregation just by exposure of UV light .…”
Section: Introductionmentioning
confidence: 99%
“…Small aromatic moieties, for example, pyrene, perylene, porphirine, can replace alkyl chain to bring tubes in solution but the higher adsorption energy makes the surfactant efficiently stick on the nanotubes and more difficult to be desorbed and removed. The choice of the aromatic core impacts the nanotube‐surfactant interaction strength and how efficiently they can be replaced with other surfactants . By incorporating an azobenzene‐derivative between head and tail, we have even been able to trigger the micelle disruption and nanotube re‐aggregation just by exposure of UV light .…”
Section: Introductionmentioning
confidence: 99%
“…Also the spectral position of the tubes’ bands highly depends on environmental effects like the surfactant used in nanotube suspension . This can be exploited to monitor the surfactant substitution: when the surfactant is exchanged, the peaks move from one position to the other . Accordingly, starting from samples solubilized using our amphiphiles α , we stepwise added SDBS to our suspensions and monitored the PL intensities at the initial positions of the maxima (highlighted by the white lines in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…α consists of a hydrophilic polyglycerol dendron for water solubility and a hydrophobic alkyl chain to attach onto the nanotube. We found that the linker between the two parts drastically influences the intensity of the interaction of the surfactants with specific laola families of nanotubes ( q = 2 n + m = fixed) . The samples were prepared in aqueous solution using an initial nanotube concentration of 0.01 g L −1 and an amphiphile concentration of 10 −4 Mol L −1 .…”
Section: Methodsmentioning
confidence: 99%
“…24). 74 The amphiphile consisting of aromatic phenyl ring spacer (15c) displayed higher replacement of starting alkyl chain amphiphile, thus, indicating an enhanced interaction with CNT. On the other hand, amphiphiles composed of triazolyl ring spacer (15b) showed negligible replacement and hence, suggesting a weaker interaction with CNT.…”
Section: Dendritic Amphiphilesmentioning
confidence: 99%